2011
DOI: 10.1007/s00223-011-9498-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Chondrocyte Maturation in the Mandibular Condyle from a Decreased Occlusal Loading Model

Abstract: Temporomandibular joint disorders (TMDs) predominantly afflict women of childbearing age. Defects in mechanical loading-induced temporomandibular joint (TMJ) remodeling are believed to be a major etiological factor in the development of TMD. The goal of this study was to determine if there are sex differences in CD-1 and C57BL/6 mice exposed to a decreased occlusal loading TMJ remodeling model. Male and female CD-1 and C57BL/6 mice, 21 days old, were each divided into two groups. They were fed either a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
4
21
0
1
Order By: Relevance
“…Dental occlusion is most important in the modulation of biomechanical loading on TMJs 39 and dietary loading is often considered as an important functional stimulation to TMJ remodeling 4,5,9,10 . Unilateral removal of teeth led to mandibular condylar cartilage thickening and sulfated glycosaminoglycans elevation 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental occlusion is most important in the modulation of biomechanical loading on TMJs 39 and dietary loading is often considered as an important functional stimulation to TMJ remodeling 4,5,9,10 . Unilateral removal of teeth led to mandibular condylar cartilage thickening and sulfated glycosaminoglycans elevation 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the small-size diet experimental group showed a lower level of decreasing condyle cartilage thickness, lower degraded cartilage areas, lower expression of ADAMTS-5 and less loss of the cartilage matrix and subchondral bone resorption, agrees with this assumption. It has been reported that although the soft diet plays a negative role in condyle development 5,9,10 , rabbits or rats that received TMJ discectomy had less degenerative cartilage changes 43,44 and higher condylar cartilage sulfate uptake 45 when fed with soft diet. Besides catabolic changes, the chondrocytes in mechanically induced degraded articular cartilage displayed the reparative capability, including the activities of phagocytizing dead cells 46 and proliferation 26,33,36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, otro estudio de Saccucci et al (2012b) determino que el tamaño y volumen condilar son significativamente diferentes en sujetos clase I, clase II y clase III lo cual puede generar la discusión sobre el papel que cumple el cóndilo en la consecutiva deformidad facial; así, el cóndilo seria capaz de generar o potenciar cierto tipo de deformidades, mientras que por otra parte, las condiciones funcionales podrían acentuar también patologías condilares como en situaciones donde la reducción de la carga oclusal permite la disminución del volumen óseo condilar en ambos sexos y la disminución de la maduración de condrocitos exclusivamente en mujeres (Chen et al 2011). Esta información redunda en una relación de causa y efecto que podría ser bidireccional en la relación de la deformidad facial y el cóndilo mandibular.…”
Section: Discussionunclassified
“…Utilizing this model, we have observed a decrease in MCC thickness in both male and female mice in response to this underloading treatment 2527 . Surprisingly, DOL reduced collagen type II (Col2) expression only in females, suggesting sex differences in the role estradiol plays in load altered load-induced MCC chondrogenesis 25, 26 . Estrogen-mediated sex differences have been previously observed in periosteal-derived tissue.…”
Section: Introductionmentioning
confidence: 99%